In Vitro regneration of three local potato (Solanum tuberosum L.) varieties of Bangladesh - Parveen, Fazlima (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2011